Received signal strength difference emitter geolocation least squares algorithm comparison - Jackson, Brad R.; Wang, S.; Inkol, R. (2011 24th Canadian Conference on Electrical and Computer Engineering(CCECE), 2011)
Approaches based on the measurement of the received signal strength difference (RSSD) for pairs of sensors offer interesting possibilities for using networks of simple sensors to geolocate radio frequency emitters. This paper compares the performance of four Least Squares-based RSSD geolocation algorithm implementations for non-cooperative emitters. Both simulated and measured data are used to compare the geolocation estimation accuracy of these algorithms. Several conclusions have been reached regarding the relative accuracy and computational cost of these algorithms.